1997
DOI: 10.1046/j.1365-2834.1997.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Contracting in the National Health Service (NHS): recognizing the need for co‐operation

Abstract: Within the reorganized National Health Service hierarchical relationships between Health Authorities and Trusts have been replaced by functional differentiation. However, differentiation of function cannot be seen as an end in itself and management of the relationship between purchasers and providers must include managing the differentiation as well as the function. This paper suggests that collaborative and administrative activities have a distinct role to play in health service management. The paper suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…There were also fears that competition had forced down prices and quality (RCN 1996) and caused unnecessary turbulence which made universities reluctant to share good practice. This echoed the problems found in contracting in the NHS (Joslyn 1997).…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…There were also fears that competition had forced down prices and quality (RCN 1996) and caused unnecessary turbulence which made universities reluctant to share good practice. This echoed the problems found in contracting in the NHS (Joslyn 1997).…”
Section: Literature Reviewmentioning
confidence: 86%
“…A key question was how close relationships should be if competition and a market were to thrive? Annandale (1995) suggested that there should be some distance, but this view was contested by those who believed there were more benefits to be had in partnership such as stability, improved quality and service development (Joslyn 1997, Council of Deans and Heads of UK University Facilities for Nursing, Midwifery and Heath Visiting 1998). Corbett (1998) asserted that NMET contracting with consortia represented ‘an interface for mutual exploitation and negotiation’ (p. 529) which should be developed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Purchaser-provider splits can lead to a failure in continuity in management, which is essential in securing effective outcomes Joslyn (1997) 165 Long-term contracts improve efficiency Two types of asset specificity are important in health care: site specificity (buyer and seller located near to each other reduces transport costs) and dedicated assets (investments by the supplier that if the contract were terminated would result in spare capacity). A long-term contract increases the likelihood that the least-cost 'transaction-specific' investment will be made rather than the lower-risk, more generalised investment Dawson and Goddard (2011) 24 The more important asset specificity is in the transaction, the longer a duration of the contract is required, until vertical integration is the most efficient arrangement Goddard and Mannion (1998) 28 …”
Section: Factors Which Influence Contractual 'Success'mentioning
confidence: 99%
“…Management writers also promoted the idea that as organisations become more complex, domain‐specific and esoteric, employees must participate in co‐ordinated decision‐making so that the old tension between professional autonomy and bureaucratic control will diminish (e.g. Cavanagh 1996; Joslyn 1997).…”
Section: The Career Of the Culture Conceptmentioning
confidence: 99%